Effects of olive cake, citrus pulp and wheat straw silage on milk fatty acid composition of Comisana ewes - Caparra P.; Foti P.; Scerra M.; Postorino S.; Vottari G.; Cilione C.; Scerra V.; Sinatra M.C. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The objective of this study was to evaluate the effects of partial replacement of conventional roughages with an ensiled-mixture made up of crude olive cake, orange pulp and wheat straw on fatty acid composition of ewe's milk. Thirty-six lactating Comisana ewes at about 150 days in milking, were divided into three homogenous groups (grass, G; silage 100, S100; and silage 50, S50) of 12 animals. Ewes of group G were allowed to graze pasture during the day and received hay plus concentrate on their return to the stall. The other two experimental groups were fed a mixed-diet containing silage, hay and concentrate. The silage was a mixture (% as fed) of 30% crude olive cake, 65% orange pulp and 5% wheat straw. The two silages differed only in the level of stone removal from the olive cake (100% in S100 and 50% in S50). The trial lasted 70 days preceded by a 21-day adaptation period to the experimental diets. Every 14 days individual milk samples of the complete morning milking were collected and analysed for fatty acid composition. In milk from S100 and S50 groups, the C18:0, C18:1 t9, C18:1 c9, C18:1 t11, C18:2 t9-c12, C20:0 and C20:3 n6 fatty acids increased significantly, while C6:0, C8:0, C10:0, C11:0, C12:0, C13:0, C14:0, C14:1, C15:0, C16:0, C18:2 c10-t12, C18:2 c9-t11 (CLA) and C18:3 n3 fatty acids decreased significantly in comparison to the G group. This trend has determined a significant decrease of the short (C6-C11) and medium-chain (C12-C17) fatty acids, an increase in UFA, in particular MUFA, and an improvement of the UFA/SFA ratio in milk of the S100 and S50 groups. The n-6 PUFA content was significantly higher in the milk of the S100 and S50 groups than in G group, while the n-3 PUFA one was significantly higher in the milk of group G. As a consequence, n-6/n-3 PUFA ratio was significantly higher in milk from S100 and S50 groups in comparison to G group.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)